EVALUATION OF PETRONAS’ STRATEGIC RESPONSES TOWARD HUMAN RIGHTS BASED INSTITUTIONAL PROCESSES - Wan Hassan, Wan Ahmad Hafiz (2013)
Recently there has been an upsurge of attention being given on the discussion of human rights and businesses, as a consequence of globalization. Traditionally it was perceived that only governments and state agents can be held responsible for human rights protection, however with ever expanding roles of multinational corporations have nowadays, businesses are gradually undertaking their social responsibility and contribute substantially towards the society. This research examines the strategic response employed by Petronas, when confronted with institutional pressures with regards to human rights issues. Views from “Institutional” and “Resource Dependence” theories have provided two different insights on how organizations could behave and respond towards their environmental factors. Cases relating to human rights issues involving Petronas and its business affiliates will be highlighted and analysed to evaluate their responsiveness toward institutional processes via a theoretical framework. Based on the findings from the analysis, it was proved that Petronas have strategically responded to human rights related institutional processes in divergent ways when operating in different business settings and environmental factors.